Clinical and radiological outcomes of hemivertebra resection for congenital scoliosis in children under age 10 years: More than 5-year follow-up. Issue 32 (7th August 2020) - Yang, Jae Hyuk; Chang, Dong-Gune; Suh, Seung Woo; Kim, Woon; Park, Jewel
Abstract : Abstract: The surgical treatment of congenital scoliosis under 10 years is difficult as it involves resecting vertebrae. Moreover, patient follow-up after surgery is extremely important because the patient is a child whose growth has not been completed. However, there are very few long-term follow-up studies after surgical treatment of congenital scoliosis. Therefore, this study is designed to evaluate surgical outcomes after posterior hemivertebra resection in children under 10 years and its long-term effects. Twenty-one patients with congenital scoliosis who were younger than 10 years at the time of the surgery and received posterior hemivertebra resection and fusion using pedicle screw fixation were included in this study. There were significant improvements in the main curve, coronal balance, sagittal vertical axis, thoracic kyphosis, and lumbar lordosis after surgery ( P < .001, .021, .047, .043, .006, respectively). Coronal balance, sagittal vertical axis, thoracic kyphosis, and lumbar lordosis remained within the normal range during the follow-up period; however, main curve deteriorated significantly ( P = .005). Trunk appearance of perception scale improved significantly after surgery ( P = .031) and was maintained during the follow-up period ( P = .078). In conclusion, posterior hemivertebra resection and fusion using pedicle screw fixation in patients under 10 years old with congenital scoliosis is a safe and effective procedure that can achieve rigid fixation and deformity correction. Complete resection of the hemivertebra is important for deformity correction and prevention of curve progression, and careful long-term follow-up is necessary.